PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR GURU SMP NEGERI DI JAKARTA SELATAN - Athina Al Yusfi (Jurnal Manajemen Pendidikan, 2016)
The purpose of this research is to determine the effect of leadership transformational and organizational commitment organizational citizenship behavior the teacher junior high shcool Jakarta..The research methodology was survey which were selected by simple random sampling technique. Analysis and interpretation of the data indicate that (1) transformational leadership has a positive direct effect in organizational citizenship behavior, (2) organizational commitment has a positive direct effect in organizational citizenship behavior, (3) transformational leadership has a positive direct effect in organizational commitment.